The Clinical and Economic Burden of Idiopathic Hypersomnia and Narcolepsy: A United States Claims-Based Analysis - Saad R; Markt SC; Lillaney P; Profant DA; Fuller DS; Poole EM; Alvord T; Prince P; Desai S; Whalen M; Ni W; Black J (Nature and Science of Sleep)
Ragy Saad,1 Sarah C Markt,1 Prasheel Lillaney,1 Deb A Profant,1 Douglas S Fuller,2 Elizabeth M Poole,1 Trevor Alvord,3 Patricia Prince,3 Shaina Desai,3 Marisa Whalen,2 Weiyi Ni,1 Jed Black1,4 1Jazz Pharmaceuticals, Palo Alto, CA, USA; 2Jazz Pharmaceuticals, Philadelphia, PA, USA; 3Aetion, Inc., New York, NY, USA; 4Stanford University Center for Sleep Sciences and Medicine, Palo Alto, CA, USACorrespondence: Jed Black, Stanford University Center for Sleep Sciences and Medicine, 401 Quarry Road, #3301, Palo Alto, CA, 94304, USA, Email jed.black@jazzpharma.comPurpose: Idiopathic hypersomnia and narcolepsy are similar but distinct sleep disorders. This study evaluated the clinical and economic burden experienced by individuals with either condition.Patients and Methods: Merative™ MarketScan® Research Databases claims were analyzed (study period, 12/31/2013– 2/29/2020). Eligible individuals were ≥ 18 years of age, continuously enrolled (365 days before/after cohort entry), and had a claim for either condition. Those with cataplexy were excluded from the idiopathic hypersomnia cohort. Individuals entered cohorts upon their earliest claim for their condition during the study period. Clinical classification categories, select conditions, healthcare resource utilization (HCRU), and medical costs were assessed over a 2-year period. Percentages of individuals with comorbid conditions were summarized. Mean (SD) HCRU and total all-cause medical costs were presented per patient per year (PPPY). HCRU and medical costs PPPY were HCRU or medical costs 365 days before/after cohort entry divided by 2.Results: 11,426 individuals with idiopathic hypersomnia and 31,214 with narcolepsy were included. Median ages were 45 and 43 years, respectively; approximately 65% of each cohort was female. Mean numbers of comorbid conditions across all categories were 15.4 (5.4) and 14.6 (5.7), respectively. Ill-defined conditions (95.6%, 94.4%), nervous system diseases (83.8%, 100.0%), and respiratory system diseases (83.6%, 79.1%) were most common broad clinical classification categories. Both cohorts experienced sleep apnea (62.8%, 52.1%), hypertension (45.7%, 42.9%), hyperlipidemia (42.2%, 38.4%), pain (66.4%, 66.0%), and mood disorders (41.9%, 43.3%). Mean all-cause outpatient visits PPPY among those with ≥ 1 visit were 28.2 (40.1) and 27.4 (40.6) for individuals with idiopathic hypersomnia or narcolepsy, respectively. Mean all-cause medical costs PPPY were $11,134 ($22,674) and $11,591 ($25,956) for individuals with idiopathic hypersomnia or narcolepsy.Conclusion: Individuals with narcolepsy and idiopathic hypersomnia experience comorbid conditions which bear consequences for healthcare systems; these may be considered when evaluating overall health of individuals with either condition.Plain Language Summary: Idiopathic hypersomnia and narcolepsy are rare diseases that affect sleep. Both diseases can make people extremely sleepy throughout the day. This study used health insurance claim records to understand the effects of these diseases on patients’ health. The health insurance claims were from December 2013 to February 2020. This study looked at other diseases that people with idiopathic hypersomnia or narcolepsy have, the number of times they saw a doctor, and how much their care cost over 2 years. This study found that people with idiopathic hypersomnia or narcolepsy also have many other conditions such as problems while sleeping, diseases of the heart and blood vessels, diseases of the metabolic system (like high cholesterol), pain, and mental illness. They also visited their doctors over 25 times on average throughout the year and had medical costs totaling about $10,000 per year on average. These results show that there is a large burden of many health conditions and a need for people with either idiopathic hypersomnia or narcolepsy to see their doctors to help understand their overall health. Keywords: hypersomnolence disorders, comorbid conditions, cardiovascular, hypertension, healthcare resource utilization, healthcare costs